Kurikulum Merdeka Sebagai Upaya Peningkatan Kualitas Pendidikan Pada Abad 21 Di Pendidikan Dasar : Kurikulum Merdeka Sebagai Upaya Peningkatan Kualitas Pendidikan Pada Abad 21 Di Pendidikan Dasar - Anwar, Muhammad Syaiful; Ratnasari, Dwi; Lestari, Diah Puji (UNIB Press, 2025)
The aim of this research is to determine the efforts of the independent curriculum in improving the quality of 21st century education, especially at the basic education level. Through the literature study method, this research analyzes the basic principles, implementation, and advantages of the independent curriculum in improving the abilities needed in the 21st century, strengthening character, and evaluating learning. The results of the study show that the independent curriculum is designed with flexibility to meet local and global needs, emphasizes project-based learning, and integrates the values ​​of the Pancasila student profile. Implementation of this curriculum provides opportunities for students to develop critical thinking, creativity, collaboration and communication competencies, while strengthening character through learning that is relevant to real life. Simplification of teaching materials and process-based evaluation allows students to learn more deeply, while teachers are given freedom in designing appropriate learning strategies. The advantages of the independent curriculum include an orientation towards holistic, adaptive and sustainable learning, so that it has the potential to improve the quality of basic education in Indonesia. It is hoped that this research will become a reference in understanding and optimizing the implementation of the independent curriculum, as well as making a significant contribution in realizing national education that is relevant to the challenges of the 21st century.